2020
DOI: 10.1108/dpm-03-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Good governance and local level policy implementation for disaster-risk-reduction: actual, perceptual and contested perspectives in coastal communities in Bangladesh

Abstract: PurposeDespite Bangladesh's great strides in formulating disaster management policies following the principles of good governance, the degree to which these policies have successfully been implemented at the local level remains largely unknown. The objectives of this study were two-fold: (1) to examine the roles and effectiveness of local-level governance and disaster management institutions, and (2) to identify barriers to the implementation of national policies and Disaster-Risk-Reduction (DRR) guidelines at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…At the same time, applying technical methods in disaster prevention puts higher requirements for learning ability and adaptability of the management subjects and objects, highlighting the importance of the dynamic adaptability of local emergency resilience. In addition, reducing compound disasters is a type of local governance [ 59 ]; full participation and collaboration of related subjects are necessary to improve governance effectiveness. In this governance process, local government plays the role of leader and coordinator and aims to realize the “1 + 1 > 2” governance efficiency through collaborating subjects and resources.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, applying technical methods in disaster prevention puts higher requirements for learning ability and adaptability of the management subjects and objects, highlighting the importance of the dynamic adaptability of local emergency resilience. In addition, reducing compound disasters is a type of local governance [ 59 ]; full participation and collaboration of related subjects are necessary to improve governance effectiveness. In this governance process, local government plays the role of leader and coordinator and aims to realize the “1 + 1 > 2” governance efficiency through collaborating subjects and resources.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the capacity was assessed by using several criteria i.e., present status of local-level Govt. and NGOs structure for disaster management (Azad et al 2019;Seddiky et al 2020;Uddin et al 2020), present status of disaster preparedness plan (Khan 2008;Huq 2016;Islam et al 2021), sound and observed legislation about DRR and disaster preparedness (Banu 2015;Naser 2015;Shahjahan et al 2016), status of diversity of livelihood options in the community (Kamal 2013;Roy and Basu 2020;Sarker et al 2020), existing Govt. resource levels to minimize disaster risk (Khan and Rahman 2007;Afrin 2018), people knowledge level of different hazards (I.…”
Section: Methods For Risk Assessmentmentioning
confidence: 99%
“…faith-based committees, social networks, school committees) play indispensable roles in maximising collective capital and taking action collaboratively at the local level. Several recent studies have confirmed that they utilise social learning processes as a pathway to enhance community resilience (Choudhury et al, 2021;Uddin et al, 2020a;Uddin et al, 2020b).…”
Section: Introductionmentioning
confidence: 93%